Energy and environmental sustainability assessment of a crude oil refinery by thermodynamic analysis. (16th September 2015) - Alhajji, Mahdi; Demirel, Yaşar
Summary This study presents the assessment of energy and environmental sustainability metrics for a crude oil refinery consisting of three distillation columns. The assessments of the current operation and the retrofits for possible improvements are suggested by the thermodynamic analysis and energy analyzer. The main objective is to explore the scope of reducing the thermal energy consumption and CO2 emissions for a more sustainable refinery operation. Thermodynamic analysis is carried out by using the thermal analysis capability of 'column targeting tool' to address the 'energy intensity metrics' and the 'energy analyzer' to design and improve the performance of the heat exchanger network system for process heat integration. Environmental pollution impact metrics are estimated from the 'carbon tracking' options with a selected CO2 emission data source of US‐EPA‐Rule‐E9‐5711 and using crude oil as a primary fuel source for the hot utilities. The results indicate that column targeting tool, energy analyzer, and carbon tracking can estimate the energy and environmental sustainability metrics of an existing design and determine the scope of considerable improvements for reducing the costs of thermal energy required and emissions of carbon dioxide in a crude oil refinery operation. Copyright © 2015 John Wiley & Sons, Ltd.